Properties Of Different Fillers In Acrylic Resin For Denture Application - Tan, Jia Sheng (Universiti Sains Malaysia, 2017)
Dental base which fabricated by Polymethyl methacrylate (PMMA) resin are commonly used due to its good physical and aesthetic properties. In this project, the aim is to identify the most suitable filler and optimum filler loading to improve PMMA resin properties. The mechanical properties of PMMA composites were determined based on flexural properties, fracture toughness, hardness and impact strength. PMMA composites were mixed by using Stryker Mixevac III bowl under vacuum condition. In the first stage, mechanical testing was carried out to determine the most suitable weight loading percentage between HA and β-TCP fillers. PMMA/2% HA composite showed better improvement than other filler loadings. Hence in the second stage, PMMA/2% HA composite was modified by various weight loading percentage of NBR and the mechanical properties, thermal stability and water absorption were measured. It is observed that no significant improvement in mechanical properties was obtained by adding NBR in PMMA/2% HA. However addition of NBR is able to increase the thermal stability and reduce water absorption. In third stages, PMMA/2% HA was added with hybrid fillers where 2% HA was hybridized with 2% PLA microsphere, untreated Al2O3 or treated Al2O3. PMMA/2% HA/2% PLA microsphere showed small improvement toward impact strength and fracture toughness while PMMA/2% HA/2% treated Al2O3 showed improvement in flexural strength. In conclusion, 2% HA filler able to increase the mechanical properties of PMMA resin significantly and the properties can be further improved by hybrid fillers